Assessment and Evaluation of the Implementation of a Vendor Management System (VMS) in Vendor Data Management Using the DeLone & McLean Method and Gap Analysis at PT PLN (Persero) - Ardhi, Irsyad; Widodo , Erwin (Journal Research of Social Science, Economics, and Management, 2026)
The management of vendor data at PT PLN (Persero) before the implementation of the Vendor Management System (VMS) faced fundamental issues, including data duplication of up to 40% among 110,936 registered vendors, data fragmentation across various applications, such as Eproc and SAP, which were not integrated with one another, and repetitive registration and evaluation processes conducted separately within each unit. This research aims to analyze the implementation of VMS in vendor data management, evaluate the quality of the system and its services, and formulate improvement strategies to optimize VMS implementation. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with eight key informants selected using purposive sampling, direct observation, and document reviews. The evaluation of the implementation was conducted using the DeLone and McLean Information Systems Success Model, which comprises six dimensions: system quality, information quality, service quality, system use, user satisfaction, and net benefits. The results indicate that VMS has been successfully implemented as a Single Source of Truth (SSoT), replacing the previous fragmented system. VMS demonstrates strong performance in terms of usability perceived by both internal and external users, while VMS Corner services are highly valued by vendors. The implementation of VMS has generated significant human resource efficiencies, including a reduction in personnel requirements from 48 employees distributed across various units to 14–16 centralized employees (a savings of 65–70%), the elimination of physical administrative costs, and improved data accuracy through a dual-verification mechanism.